(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Entrepreneurship is a new and powerful path and is the key Nation’s development. It can be assumed that marketing is a potent tool for economic development in an agricultural country like India. In India, women constitute half of the country’s population, so the development of women entrepreneurship is an important part of the country’s development. MSMEs are considered the backbone of India’s economic growth and development. This spring, imp active measures need to be taken to ensure job knowledge, training and skill development for women. The untapped skills of young women can be identified, trained and used in various sectors to create a positive impact on the economy. This article tests the concepts of entrepreneurship and women entrepreneurship, the issues and threats confronts by women entrepreneurs in India, the virtues of Indian women mother entrepreneurs and tips for developing women entrepreneurs.